The Factors that Related with Occurrence Food Waste of Diabetes Militus Patients - Ajib Jayadi; Dewi Woro; Asep Jalaludin Saleh (CV. Global Health Science Group, 2021)
According to the survey, the percentage of food waste’s diabetes militus patients in the Imanuel Hospital of Bandar lampung still have not reached the minimum service standars. This study aimsed to analyze the factors associated with food waste in diabetes militus patients in Hospital Imanuel. This is a descriptive analytic study using a cross sectional research design. The sample of this study was 50 patients who suffered diabetes mellitus and were hospitalized. The sample is taken = by purposive sampling. The Analysis of the relationship between the dependent variable and the independent variable is done by using the chi square test. Data on age, gender, appearance of food, taste of food and attitude of officers were obtained through a questionnaire while leftover food was obtained through the Comstock form. Of the totat sampels from 50 th 46% 56 years old, and 78% sex women.The results of correlation test there is a significant association between appearance of food (p value 0,005) and taste of food (p value 0,002) with the food waste. There were no significant associations between service providers (p value 0,776) with the food waste.